Histological Evaluation of Root Canals by Performing a New Cleaning Protocol "RUA" in Endodontic Surgery - Alfredo Iandolo; Alessandra Amato; Massimo Pisano; Giuseppe Sangiovanni; Dina Abdellatif; Roberto Fornara; Michele Simeone (MDPI AG, 2023)
Aim: To enhance cleaning during retro-preparation in endodontic microsurgery. Materials and Methods: Forty mandibular premolars were instrumented, filled with a single cone technique, and then retro-preparation was performed and assigned to experiment A. In group A1, the cavity created by the retro preparation was cleansed with 2 mL of normal sterile saline. In group A2, the retro cavity was cleaned with 2 mL of sterile saline after the retro preparation. All the irrigation solutions mentioned above were delivered using an endodontic needle with a lateral vent and a gauge of 30. Subsequently, in group A2, 17% EDTA gel and 5.25% gel were inserted into the cavity and activated using ultrasonic tips. After the irrigation protocols, the specimens were decalcified for histological evaluation. Results: In the experiment, the amount of hard tissue debris was significantly greater in group A1 compared to group A2 (p < 0.05). Conclusions: The samples in group A2, where the new protocol was performed, showed statistically significant results.